Assist-as-needed control strategies for upper limb rehabilitation therapy: a review - Ahmed Mounis, Shawgi Younis; Zainul Azlan, Norsinnira (UTM Press, 2019)
Stroke is one of the leading causes for disabilities that can damage the functional capabilities of survivors and significantly affects their ability to perform activities of daily living. In recent years, assist-as-needed (AAN) strategy has received significant attention because it can encourage the stroke subjects to achieve functional recovery for the loss of motor function. However, the implementation of AAN strategy only becomes possible when the subjects’ functional ability is known. Thus, inaccurate and inconsistent estimation of subjects’ functional movement or motor ability is crucial and has been a major limitation for the current implementation of AAN. The existing gap in literature between the current robotic approach and clinical practices is also another important concern that can lead to conflict in the near future. This paper aims to provide an overview of the AAN control strategies and estimation techniques found in the research literature. Hence, an overview of specific clinical practices in functional motor assessment and estimation procedure that runs parallel to the robotic system counterpart is also designed to provide the significance and challenges in bridging the gap between robotic and clinical practices. This review concludes with major findings in the state-of-the-art in AAN robotic therapy and outlines the procedures for clinical adoption. This study finds the necessity of further research required to determine the effectiveness of clinical assessment procedure alongside with the robotic therapy that can address this need by providing a consistent and accurate estimation of subjects’ functional ability.